Effect of Corporate Social Responsibility Disclosure on Financial Performance with Audit Quality as a Moderating Variable - Kartika Dewi; Monalisa Monalisa (Binus Business Review, 2016)
This article aimed to examine the influence of Corporate Social Responsibility (CSR) disclosure to the financial performance proxy on Return on Assets (ROA), Return on Equity (ROE), and company value proxy on Price to Book Value (PBV) empirically as well as knowing the existence of the audit quality as moderating variable whether it will affect the relationship between CSR disclosure on ROA, ROE, and PBV. The object of this study was mining companies listed on the Indonesia Stock Exchange period 2010-2012. The sample was selected using a purposive sampling method and obtained samples as many as 26 companies with a total data of 78 data. Hypothesis testing methods used were simple regression analysis and moderated regression analysis. The results of this study showed that Corporate Social Responsibility (CSR) disclosure had an effect on ROA, but had no effect on ROE and PBV, and audit quality as a moderating variable could not affect the relationship of CSR disc losure on ROA, ROE, and PBV.